A solid-state platform for quantum technologies. (Research'eu results magazine)
EU-funded researchers have pioneered the coupling of single artificial atoms to photons within optical microcavities. Systems like quantum dots are essential building blocks for quantum information technologies, and a means to generate pure single photons on demand.